The Empire of Beasts Then and Now: Political Cartoons and New Trends in Victorian Animal Studies - Irina Kantarbaeva-Bill (Cahiers Victoriens et Edouardiens)
Victorians were obsessed with animals and used them pervasively in fiction and press as proxies for human races. This article attempts to analyse the animal display as a political commentary in the visual images of Punch or The London Charivari Magazine in the aftermath of the 1857 Mutiny and the growing geopolitical tensions worldwide. In exhibiting and displaying such animals as the lion, the tiger, the crocodile and the bear while dealing with colonial issues, the popular British cartoons acted as complex rhetorical structures that helped to powerfully influence mass opinion and consequently harnessed the public support for the Empire. Non-human animals were not just used for rhetorical purposes: beasts provided their very bodies to fund and fuel imperial projects, carried administrators and armies across and into remote spaces, and instilled fear and fascination in colonized and colonizers alike. While the scholarship recounting this relationship is not new, recent studies built on pioneering environmental and cultural histories (re)introduced many of the salient topics related to the showcasing of animals and imperialism such as conquest, disease, breeding, scientiﬁc categorization, animal welfare, vivisection, zoos, hunting, and conservation.